Analysis of The Implementation of Qur'an Learning Using The Iqra' Method in Elementary Schools - Putri Nur Wahyu Romadhona; Romelah; Dina Mardiana (Cendekia, 2025)
This study analyzes the effectiveness of the Iqra method in improving elementary school students' reading ability in the public school environment. It aims to explore how the Iqra method can be adapted in the formal education system, especially in the context of public elementary schools, which have limited religious lesson hours and heterogeneous student reading abilities. This study uses a qualitative approach with a case study design. Data was collected through classroom observations, in-depth interviews with teachers and students, and analysis of documents related to learning the Qur'an. The study results show that the Iqra' method applied systematically, combined with interactive learning media and formative-based evaluation systems, significantly improves students' Qur'an reading ability. Students who initially had difficulties in recognizing and prociting hijaiyah letters showed a gradual improvement in fluency and reading accuracy after participating in Iqra'-based learning. These findings confirm that the Iqra' method is not only effective in non-formal educational environments such as TPA, but can also be optimally implemented in the public elementary school system with the right strategy. This study has a scientific contribution by highlighting how the Iqra' method can be integrated in formal education systems with structural limitations, which has been rarely studied in previous studies.